2004
DOI: 10.1002/rcm.1580
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of t,t‐muconic, S‐phenylmercapturic and S‐benzylmercapturic acids in urine by a rapid and sensitive liquid chromatography/electrospray tandem mass spectrometry method

Abstract: We describe a rapid and sensitive high-performance liquid chromatography/electrospray tandem mass spectrometry (HPLC/ESI-MS/MS) method for simultaneous determination of the most relevant metabolites of benzene and toluene, t,t-muconic acid (t,t-MA), S-phenylmercapturic acid (S-PMA), and S-benzylmercapturic acid (S-BMA). Urine samples were purified before analysis by solid-phase microextraction (SPE) on SAX cartridges with 50 mg sorbent mass. The developed method fulfils all the standard requirements of precisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…The analysis time was 15 min with a lower limit of quantitaion (LLOQ) of 0.4 ng/mL. Another method used 96-well SAX solid-phase extraction and achieved an LLOQ of 0.5 ng/mL but with a long analysis time of 26 min (Barbieri et al, 2004). Pieri et al (2003) reported a method using HPLC purification instead of commonly used solid phase and liquidliquid extraction to clean up the sample.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis time was 15 min with a lower limit of quantitaion (LLOQ) of 0.4 ng/mL. Another method used 96-well SAX solid-phase extraction and achieved an LLOQ of 0.5 ng/mL but with a long analysis time of 26 min (Barbieri et al, 2004). Pieri et al (2003) reported a method using HPLC purification instead of commonly used solid phase and liquidliquid extraction to clean up the sample.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of this assay was evaluated in human urine specimens from smokers and nonsmokers serving as benzene-exposed and nonexposed groups respectively. Barbieri et al 64 also used LC/MS/MS for determination of t,t-MA and S-PMA in urine samples after SPME based purification. The limit of detection was found to be 6 mg/dm 3 for t,t-MA and 0.3 mg/dm 3 for S-PMA.…”
Section: Analysis Of Metabolitesmentioning
confidence: 99%
“…On the other hand, there has been widespread use of high performance liquid chromatography (HPLC) with reverse phase columns and ultraviolet and visible spectrophotometry (UV-VIS) or mass spectrometry (MS) detection [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. One way to separate anions by chromatography is to use cation exchange columns where the ions are separated by ion exclusion.…”
Section: Introductionmentioning
confidence: 99%